Asuhan Kebidanan Komunitas pada Keluarga Tn Z dengan Menorhagea pada Remaja Putri di Dusun Ngalong Desa Kuta Kecamatan Pujut - Sri Hastuti; Elly Sustiyani (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2025)
This study aims to improve the health status of families so that a healthy and prosperous family is realized in the family of Mr. "Z" with menorrhagia in adolescent girls in Ngalong Hamlet, Kuta Village, Pujut District. The study was carried out by collecting all available data sheet formats through interview techniques and systemic observation. Subjective data, especially on the main complaint of menstruation for more than 10 days and changes, Blood Pressure (BP): 98/80 mmHg, Respiration (P): 18 x / i, Pulse (N): 88 x / i, Temperature (S): 36.5o C, eyes are not edematous, pale conjunctiva, white sclera. The potential diagnosis in this case is endometrium but it did not occur because it has been handled properly. Immediate action that can be taken is to collaborate with health workers and patients. The planning carried out on Ms. M aged 14 years is: informing about the results of the examination, explaining the signs and symptoms, handling menorrhagia and consulting a Sp.OG doctor. The implementation given to Ms. M with Hypermenorrhea is: informing about the results of the examination that Ms. M's general condition informs about the results of the examination, explains the signs and symptoms, treatment of menorrhagia, and consultation with a Sp.OG doctor. Evaluation is a stage of assessment of the success of the maintenance given in overcoming consultation with a Sp. DAN doctor.